2022
DOI: 10.4102/rw.v13i1.327
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting Grade 6 learners’ reading performance in a rural school in Maluti, South Africa

Abstract: Background: Rural learners face severe reading challenges that are unique to their environment. The challenges include parents’ low level of education, little or no parental support, lack of reading material, and parents’ low socio-economic status. It is therefore important that rural education research highlights these challenges in order to help in addressing them.Objectives: The study sought to explore the factors affecting the reading performance of Grade 6 learners from the Maluti District in the Eastern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…These skills are integrated alongside the readers' knowledge of the world and understanding of how texts work and so is a dynamic and active process, requiring the reader to constantly adjust thinking as each new word, sentence and paragraph is read (Duke and Cartwright, 2021; Fatyela et al, 2021; Pretorius and Lephalala, 2011). The reader's knowledge of the world and text is situated in the context in which reading takes place and this further impacts on the meaning making process (Cekiso et al, 2022; Hogan et al, 2011). In addition, a teacher's pedagogic skill and knowledge further impacts on learners' acquisition and application of the skills and strategies required for reading comprehension (Cilliers et al, 2022; Moats et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These skills are integrated alongside the readers' knowledge of the world and understanding of how texts work and so is a dynamic and active process, requiring the reader to constantly adjust thinking as each new word, sentence and paragraph is read (Duke and Cartwright, 2021; Fatyela et al, 2021; Pretorius and Lephalala, 2011). The reader's knowledge of the world and text is situated in the context in which reading takes place and this further impacts on the meaning making process (Cekiso et al, 2022; Hogan et al, 2011). In addition, a teacher's pedagogic skill and knowledge further impacts on learners' acquisition and application of the skills and strategies required for reading comprehension (Cilliers et al, 2022; Moats et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In South Africa, Cekiso, et al's study (2022) revealed that several factors, including parents' low levels of education, an unfavourable home environment, their socioeconomic status, and a lack of reading materials at home and at school, had an impact on the reading performance of students from rural areas. The current study focused on grade three LWD rather than the same age developing peers examined in the Cekiso, et al, (2022) study. In the current study on the effects of age on the effectiveness of mnemonics on the enhancement of reading abilities among grade three LWD, the quantitative results revealed that many grade three LWD preferred using mnemonics because this memorization technique helped individuals to learn, retain and recall information.…”
Section: Introductionmentioning
confidence: 99%
“…Failure of learners have been attributed to different factors such as lack of infrastructure (Barrett et al, 2019), socio-economic background of learners’ family (Gobena, 2018), lack of parents’ involvement (Cekiso et al, 2022), among others. However, not much seems to have been stated with regards to leadership in terms of rapid curriculum change and delivery.…”
Section: Introductionmentioning
confidence: 99%